THE BRONFRENBRENNER’ ECOLOGICAL MODEL AS THEORETICAL FRAMEWORK OF THE PSYCHOONCOLOGY - Torrico Linares, Esperanza; Santín Vilariño, Carmen; Andrés Villas, Montserrat; Menéndez Álvarez-Dardet, Susana; López López, María José (Anales de Psicología / Annals of Psychology, 2002)
The Psychooncology is a recent discipline that lacks an own theoretical mark. In their place she has left nurturing of other disciplines of the Psychology like the Psychopathology or the Psychology of the Health. We outline in our work that a valid alternative to confront the treatment and mainly the investigation with patient oncológicos could be the Ecological Model of Bronfrenbrenner. This model allows us to evaluate and to intervene in all those variables that impact direct or indirectly on the patient. Variables that will be decisive when that the person adapts to her illness and that in many occasions we forget when we plan an intervention or investigation.